INTERPOLATOR IN BATHYMETRIC MAP CONTOURING - Ernawati Sengaji; Bisman Nababan (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2009)
A digital bathymetric model may be produced after sounding point interpolated by using specific methods. There are three common interpolation methods used recently: inverse distance to power, kriging and minimum curvature. This study applied two scenarios of data processing to compare those three methods on producing bathymetric contours. Numeric validation was performed on the three different gridding methods. The result of this study showed that kriging method was spatially more effective in interpolating water depth than that of the other two.Keywords: interpolation, kriging, inverse distance to power, minimum curvature, bathymetry